(untitled) (Journal of Engineering, 2016)
The effect of refrigerant injection techniques on the performance of heat pump system based on exergy analysis was studied theoretically. Three refrigerant injection techniques were used; the first was achieved by injected vapour in volume ratios from 1 to 7% in the accumulator. The second was injection liquid refrigerant in the discharge line with the aid of Liquid Pressure Amplification (LPA) pump, with volume ratios from 1 to 10%. The third was a hybrid injection with volume ratios of injected vapour and liquid varied from 1 to 3% and 1 to 10%; respectively. The following improvements in cycle performance were observed. For vapour injection technique, the best ratio of injection was 5%, the exergy destruction reduced by 21% and exergy efficiency enhanced by 14.6%. For liquid injection technique the best ratio of injection was 6%, the reduction in exergy destruction was 34% while the exergy efficiency increased by about 21.4%. The hybrid injection technique increased the exergy efficiency by 23% when the volume ratio of vapour and liquid injections are 3% each. The effect of condensing pressure on the cycle performance was studied also. The optimum exergy efficiency of the cycle was 54.55% achieved when the condensing pressure was 15 bars.